2021
DOI: 10.3390/foods10040801
|View full text |Cite
|
Sign up to set email alerts
|

Flavor and Metabolite Profiles of Meat, Meat Substitutes, and Traditional Plant-Based High-Protein Food Products Available in Australia

Abstract: Demand for plant-based proteins and plant-based food products is increasing globally. This trend is driven mainly by global population growth and a consumer shift towards more sustainable and healthier diets. Existing plant-based protein foods and meat mimetics often possess undesirable flavor and sensory properties and there is a need to better understand the formation of desirable meat-like flavors from plant precursors to improve acceptance of novel high-protein plant foods. This study aimed to comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 74 publications
0
24
1
Order By: Relevance
“…In addition, the sour and nutty attributes were on the positive side, while salty, chicken flavor, and savory were on the negative side. Salty taste is well-liked in chicken products [ 43 ], while sour and nutty are associated with plant-based proteins [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the sour and nutty attributes were on the positive side, while salty, chicken flavor, and savory were on the negative side. Salty taste is well-liked in chicken products [ 43 ], while sour and nutty are associated with plant-based proteins [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with similar reports, it is found that the main VOCs of natto are the same but also different, reflecting both commonness and individuality. For example, Kaczmarska et al [ 35 ] found the volatile profile of the natto was dominated by alkylpyrazines and ketones. Chen et al [ 7 ] found that the main VOCs in natto were esters, ketones, pyrazines, and phenols.…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies characterising flavour development of fermented PBMAs are much fewer than that for meat alternatives. 22 Kaczmarska et al 23 investigated the chemical composition and sensory profile of various meat analogues, as well as fermented plant products such as tempeh and tofu, which are often regarded as meat-like substitutes. The results showed that only a few alternatives had a sensory profile vaguely resembling a meaty taste, and vastly different flavor profiles.…”
Section: Importance Of Microbial Fermentation For Flavour Formation I...mentioning
confidence: 99%